2018
DOI: 10.1080/00498254.2018.1427905
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanisms of Genkwa Flos hepatotoxicity by a cell metabolomics strategy combined with serum pharmacology in HL-7702 liver cells

Abstract: 1. To investigate Genkwa Flos hepatotoxicity, a cell metabolomics strategy combined with serum pharmacology was performed on human HL-7702 liver cells in this study. 2. Firstly, cell viability and biochemical indicators were determined and the cell morphology was observed to confirm the cell injury and develop a cell hepatotoxicity model. Then, with the help of cell metabolomics based on UPLC-MS, the Genkwa Flos group samples were completely separated from the blank group samples in the score plots and seven u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[8] Both animal experiments in vivo and cell experiments in vitro indicated that excessive or long-term use of the raw Genkwa Flos could result in serious damage to liver. [9,10] As a representative Chinese traditional medicine causing drug-induced liver injury, Genkwa Flos was selected to be used as a moulding agent which induce the liver injury of rats in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Both animal experiments in vivo and cell experiments in vitro indicated that excessive or long-term use of the raw Genkwa Flos could result in serious damage to liver. [9,10] As a representative Chinese traditional medicine causing drug-induced liver injury, Genkwa Flos was selected to be used as a moulding agent which induce the liver injury of rats in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the levels of several endogenous metabolites might change when liver suffers from injury. According to the relative literatures, [10,[12][13][14] 5-oxoproline, phenylalanine, tryptophan, C 18 -phytosphingosine, LPC (16 : 0) and LPC (18 : 1) were found to be strongly associated with liver injury. As a significant intermediate of the glutathione synthesis pathway, 5-oxoproline is considered as a potential biomarker for excessive depletion of glutathione and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…There is a major challenge in the concurrent extraction, separation, and detection of cells because the endogenous metabolites vary widely in their physical and chemical properties in comprehensive characterization of the cell metabolome. 23,24 The chemical properties of a great number of metabolites are still unknown, leading to some difficulty in the problem of standardizing quenching and extraction methods. Some standard compounds are not yet readily available.…”
Section: Cell Metabolomics Prospectsmentioning
confidence: 99%
“…Recent years, a number of studies have been conducted to explore the metabolic mechanisms of TCMinduced nephrotoxicity and hepatotoxicity based on metabolomics strategies, and the satisfactory results indicated the applicability of metabolomics strategies. 5,12 Selecting an appropriate analytical platform is critical to the results. Currently, metabolomic analytical platforms used in the majority of studies are nuclear magnetic resonance (NMR), liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS).…”
Section: Introductionmentioning
confidence: 99%